2019
DOI: 10.1186/s12864-019-5781-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a milk protein transcript depletion method for differential transcriptome analysis in mammary gland tissue

Abstract: Background In the mammary gland transcriptome of lactating dairy cows genes encoding milk proteins are highly abundant, which can impair the detection of lowly expressed transcripts and can bias the outcome in global transcriptome analyses. Therefore, the aim of this study was to develop and evaluate a method to deplete extremely highly expressed transcripts in mRNA from lactating mammary gland tissue. Results Selective RNA depletion was performed by hybridization of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The APOB gene is predominantly expressed in the liver and small intestine with the alternative predominant isoforms in the small intestine (APOB-48) and liver (APOB-100) as reviewed by Whitfield et al 60 . This is confirmed by whole transcriptome RNAseq data analyses of blood and mammary gland samples from CDC and CDF cows in this study, which did not show indication of APOB gene expression ( 61 , data not shown). The APOB gene is known for a tissue-specific posttranscriptional mRNA editing in the small intestine 62 , which creates a premature stop codon and is responsible for producing the truncated APOB-48 protein in intestine tissue.…”
Section: Discussionsupporting
confidence: 77%
“…The APOB gene is predominantly expressed in the liver and small intestine with the alternative predominant isoforms in the small intestine (APOB-48) and liver (APOB-100) as reviewed by Whitfield et al 60 . This is confirmed by whole transcriptome RNAseq data analyses of blood and mammary gland samples from CDC and CDF cows in this study, which did not show indication of APOB gene expression ( 61 , data not shown). The APOB gene is known for a tissue-specific posttranscriptional mRNA editing in the small intestine 62 , which creates a premature stop codon and is responsible for producing the truncated APOB-48 protein in intestine tissue.…”
Section: Discussionsupporting
confidence: 77%
“…We chose to address these objectives using the α‐casein gene (Figure S1) which is among the most highly expressed genes in eukaryotic cells [ 17 ] and may therefore provide an excellent platform for the expression of recombinant proteins in milk.…”
Section: Resultsmentioning
confidence: 99%
“…[15] The casein proteins together account for up to 80% of total milk protein and 70% of total mammary gland mRNA in cattle. [16,17] Caseins are highly phosphorylated, associate with calcium in mammary epithelial cells and are secreted into milk in the form of a casein micelle. [18] Different caseins play distinct roles in micelle formation.…”
mentioning
confidence: 99%
“…In vivo research has been conducted to investigate the pathophysiology of the udder, in order to understand the interactions between the individual factors of bovine mastitis (Moosavi et al, 2014;Brodhagen et al, 2019;Schmenger et al, 2020). The results of these studies provide the most comprehensive insight into the infection process of bovine mastitis; however, to obtain sample material for investigation, infected animals must be euthanized (Petzl et al, 2008;Whelehan et al, 2011;Brodhagen et al, 2019). To combine the advantages of in vitro and in vivo approaches in studies, precision-cut tissue slices can be used.…”
Section: Introductionmentioning
confidence: 99%